The role of productivity coalitions in building a 'high road' competitive strategy: The case of Denmark and Ireland. (June 2013) - McLaughlin, Colm
This article draws on the concept of 'productivity coalitions' to assess the micro-foundations of Danish and Irish social partnership, and the extent to which they have facilitated a sustainable, 'high road' national competitive strategy. It focuses on continuous training to analyse the conditions necessary for effective collaboration between employers and unions. Four key variables that underpin strong productivity coalitions are identified: non-market coordination mechanisms, union 'embeddedness', ideological concordance and institutional constraints. The implications are pessimistic for effective collaboration in liberal market economies.